PERAN PENTING PERANCANGAN INTERIOR PADA STORE BASED RETAIL - Kusumowidagdo, Astrid (Dimensi Interior, 2005)
Retail business is one of the most dynamic industries that is influenced by social and economic condition of the people, demography and change of life style. No wonder better economical development will cause more shopping centres spread rapidly. In such competitive condition, retailers shall be able to apply proper retail strategies. One of the strategies that may be applied is to plan the proper store interior design. New form and style and creative ideas of the physical condition of stores that may make customers shop conveniently in a store should be taken into consideration. In customers perspective sore atmosphere strongly affects the image of a store and may stimulate customers to enter the store, and then it can be followed by further interaction up to the process of buying. Abstract in Bahasa Indonesia : Retail merupakan industri yang dinamis. Kondisi sosial, ekonomi dan demografi serta perubahan life style berpengaruh terhadap kegiatan retail. Sehingga dengan perkembangan ekonomi yang cukup meningkat, bermunculan berbagai pusat perbelanjaan. Dengan kondisi kompetitif ini, maka retailer harus mampu menerapkan strategi retail yang tepat. Salah satu strategi yang dapat dipergunakan adalah merencanakan interior toko dengan bentuk dan konsep baru serta ide-ide kreatif yang membangun citra toko. Citra toko di mata pengunjung dapat menjadi stimuli untuk masuk ke dalam toko, yang berlanjut pada proses interaksi hingga pembelian. Kata kunci: perancangan interior, store based retail, citra toko.